Comparative analysis of the Bioethanol production from verities of millet husk - Shakhi Dubey (AG Volumes, 2023)
About 10% of the world's main energy needs may be met by bioethanol. Bioethanol has considerable potential to replace the global supply of energy in the face of increasing crude oil costs, depleting resources, the political instability in producing nations, and environmental issues. Plant biomass is the renewable and plentiful source of energy-rich carbohydrates that can be easily transformed by microorganisms into biofuels, one of which is bioethanol, which is already produced on a large scale in many countries. Due to its qualities, bioethanol has been heralded as the most viable biofuel to replace gasoline. Because of its poor volumetric energy density, it requires much more bioethanol per kilometer than regular gasoline. This study will examine the production of bioethanol from the millet husk and the significance of this process.